Emergency balloon dilation or stenting of critical coarctation of aorta in newborns and infants: An effective interim palliation - Francis Edwin; Gayathri S; Vaidyanathan Balu; Kannan B.R.J; Kumar R (Wolters Kluwer Medknow Publications, 2009)
Background: Management of native uncomplicated coarctation in neonates remains controversial with current evidence favoring surgery. The logistics of organizing surgical repair at short notice in sick infants with critical coarctation can be challenging. Methods and Results: We reviewed data of 10 infants (mean age of 2.9 ±1.6 weeks) who underwent catheter intervention for severe coarctation and left ventricular (LV) dysfunction between July 2003 and August 2007. Additional cardiac lesions were present in 7. Mean systolic gradient declined from 51±12 mm Hg to 8.7±6.7 mm Hg after dilation. The coarctation segment was stented in five patients. Procedural success was achieved in all patients with no mortality. Complications included brief cardiopulmonary arrest (n =1), sepsis (n = 1) and temporary pulse loss (n = 2). LV dysfunction improved in all patients. Average ICU stay was 5±3.4 days and hospital stay was 6.5±3.4 days. On follow-up (14.1±10.5 months), all developed restenosis after median period of 12 weeks (range four to 28 weeks). Three (two with stents) underwent elective coarctation repair, two underwent ventricular septal defect (VSD) closure and coarctation repair and one underwent pulmonary artery (PA) banding. Two patients who developed restenosis on follow-up were advised surgery, but did not report. Two (one with stent) underwent redilatation and are being followed with no significant residual gradients. Conclusion: Balloon dilation ± stenting is an effective interim palliation for infants and newborns with critical coarctation and LV dysfunction. Restenosis is inevitable and requires to be addressed.